2023
DOI: 10.3390/ijerph20085597
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional Skills, Career Adaptability, and Agentic School Engagement of First-Year High School Students

Abstract: The transition to the first year of high school constitutes a critical moment because it corresponds to the implementation of a career choice, which can impact students’ satisfaction and psychosocial adjustment. The career construction model of adaptation holds potential to explain how students adapt to high school, by suggesting linkages among adaptive readiness, resources, responses, and results. However, research applying the career construction model to school transitions, combining social-emotional, caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Un estudio de Trigueros et al (2020) reveló una conexión positiva entre la inteligencia emocional y las habilidades sociales, destacando que los estudiantes con una mayor inteligencia emocional son menos propensos al acoso escolar. Esta estrecha relación entre la competencia emocional y las relaciones interpersonales saludables se refuerza en el estudio de Oliveira et al (2023), que demuestra que las habilidades sociales y emocionales, junto con la capacidad de adaptación profesional, influyen en el compromiso activo de los estudiantes. Este estudio sugiere que estas habilidades no solo son cruciales para el bienestar individual, sino que también juegan un papel en el compromiso educativo.…”
Section: Introductionunclassified
“…Un estudio de Trigueros et al (2020) reveló una conexión positiva entre la inteligencia emocional y las habilidades sociales, destacando que los estudiantes con una mayor inteligencia emocional son menos propensos al acoso escolar. Esta estrecha relación entre la competencia emocional y las relaciones interpersonales saludables se refuerza en el estudio de Oliveira et al (2023), que demuestra que las habilidades sociales y emocionales, junto con la capacidad de adaptación profesional, influyen en el compromiso activo de los estudiantes. Este estudio sugiere que estas habilidades no solo son cruciales para el bienestar individual, sino que también juegan un papel en el compromiso educativo.…”
Section: Introductionunclassified
“…Zhou believed that work adaptability is an important predictor of occupational mental health, and the higher the level of work adaptability, the better the mental health of individuals, and the better the career success [ 39 ]. It has been suggested that career adaptation of adolescents can play a protective role in reducing career decision-making difficulties, and mental health problems [ 40 ].…”
Section: Introductionmentioning
confidence: 99%